Risk preferences at the time of COVID-19: An experiment with professional traders and students - Marco Angrisani; Marco Cipriani; Antonio Guarino; Ryan Kendall; Julen Ortiz de Zarate Pina (Federal Reserve Bank of New York, 2020)
We study whether the COVID-19 pandemic has impacted risk preferences, comparing the results of experiments conducted before and during the outbreak. In each experiment, we elicit risk preferences from two sample groups: professional traders and undergraduate students. We find that, on average, risk preferences have remained constant for both pools of participants. Our results suggest that the increases in risk premia observed during the pandemic are not due to changes in risk appetite; rather, they are solely due to a change in beliefs by market participants. The findings of our paper support the traditional view that, at least on average, risk preferences are not affected by economic or social circumstances.
Keywords: D81; D91; N0; 330; risk aversion; financial markets professional; COVID-19; experimental economics